2018
DOI: 10.1038/s41556-018-0118-z
|View full text |Cite|
|
Sign up to set email alerts
|

Aspartate is a limiting metabolite for cancer cell proliferation under hypoxia and in tumours

Abstract: As oxygen is essential for many metabolic pathways, tumour hypoxia may impair cancer cell proliferation. However, the limiting metabolites for proliferation under hypoxia and in tumours are unknown. Here, we assessed proliferation of a collection of cancer cells following inhibition of the mitochondrial electron transport chain (ETC), a major metabolic pathway requiring molecular oxygen. Sensitivity to ETC inhibition varied across cell lines, and subsequent metabolomic analysis uncovered aspartate availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
275
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(321 citation statements)
references
References 36 publications
24
275
0
2
Order By: Relevance
“…Among these metabolites, we found Asp production by CAF crucial to sustain CCs proliferation. Consistent with these results, recent reports have shown that aspartate acquisition is a metabolic limitation encountered by tumors in their native in vivo environment and that overcoming this limitation is advantageous for tumour growth(Garcia-Bermudez et al, 2018; Sullivan et al, 2018). Together, our results clarify the importance of Asp in tumor progression and demonstrate a fine-tuneable mechanism by which CCs are able to adjust their Asp needs depending on tumor niche stiffness.…”
Section: Discussionsupporting
confidence: 79%
“…Among these metabolites, we found Asp production by CAF crucial to sustain CCs proliferation. Consistent with these results, recent reports have shown that aspartate acquisition is a metabolic limitation encountered by tumors in their native in vivo environment and that overcoming this limitation is advantageous for tumour growth(Garcia-Bermudez et al, 2018; Sullivan et al, 2018). Together, our results clarify the importance of Asp in tumor progression and demonstrate a fine-tuneable mechanism by which CCs are able to adjust their Asp needs depending on tumor niche stiffness.…”
Section: Discussionsupporting
confidence: 79%
“…More specifically, we observed increased vascular endothelial growth factor A (VEGFA) mRNA levels after combinational treatment in PC3 cells (Fig EV4A), in line with previous observations that suggested a negative correlation between VEGFA and aspartate level (Garcia‐Bermudez et al , ). Moreover, the decreased mRNA level of lactate dehydrogenase A (LDHA) can explain the depletion in lactate level measured by metabolites profiling (Fig E).…”
Section: Resultssupporting
confidence: 91%
“…SLC1A3 is mainly expressed in brain tissues (Fig EV1C), critical for the termination of excitatory neurotransmission (Kanai et al , ). Recent studies have highlighted the importance of SLC1A3‐mediated aspartate uptake for cancer cell proliferation under hypoxia and crosstalk between cancer cells and cancer‐associated fibroblasts in the tumor niche (Alkan et al , ; Garcia‐Bermudez et al , ; Sullivan et al , ; Tajan et al , ; Bertero et al , ). We also observed elevated SLC1A3 RNA levels in several tumor types from the TCGA database [especially kidney renal clear cell carcinoma (KIRC, P = 5.5 × 10 −30 ), kidney renal papillary cell carcinoma (KIRP, P = 2.1 × 10 −10 ), liver hepatocellular carcinoma (LIHC, P = 3.2 × 10 −10 ), and stomach adenocarcinoma (STAD, P = 6.1 × 10 −5 )] (Fig EV1D).…”
Section: Resultsmentioning
confidence: 99%
“…However, the primary substrate for oxidation in cancer cells is often not glucose but glutamine, indicating that aerobic glycolysis is not a replacement but a parallel process (Sullivan, 2015). Under oxidation deficiency such as in the case of electron transport chain inhibition and hypoxia, L‐aspartate serves as a limiting metabolite for cancer cell proliferation and adenine nucleotide synthesis (Garcia‐Bermudez et al, 2018; Sullivan et al, 2015). L ‐asparagine, which is synthesized from L‐aspartate, plays a critical role in the regulation of cellular adaptation to glutamine depletion (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%